Analisis Pengaruh Ukuran Perusahaan, Leverage, Profitabilitas, Manajemen Laba Terhadap Pengungkapan Corporate Social Responsibility (CSR)(Studi Empiris pada Perusahaan Manufaktur Tahun 2013-2015) - Usada, Wursita, Drs, Agus Endro Suwarno, MSi (2017)
Corporate Social Responsibility (CSR) is a corporate responsibility not only to its owners or shareholders but also to the relevant stakeholders and / or affected by the existence of the company. The purpose of this study was to determine the effect of firm size, leverage, profitability, earning management to the disclosure policy of corporate social responsibility (CSR) to the companies listed in Indonesia Stock Exchange. The population of this study is manufacturing companies listed in Indonesia Stock Exchange during the period 2013-2015. Data collected by purposive sampling method, as many as 138 companies obtained a sample of. Analysis using multiple linear regression. The analysis show that the variables of firm size, profitability has significant influence to the disclosure of Corporate Social Responsibility (CSR) on manufakur companies listed in Indonesia Stock Exchange in the year 2013 to 2015. Meanwhile, the variables of leverage, earning management do not have any influence to the disclosure of Corporate Social Responsibility (CSR) on manufakur companies listed in Indonesia Stock Exchange in the year 2013 to 2015. Keywords: Corporate Social Responsibility, firm size, leverage, profitability, earning management.